AFRICAN BITTER LEAF EXTRACT EFFECT ON EPITHELIUM THICKNESS OF SEMINIFEROUS TUBULES IN WISTAR RATS WITH DIABETES MELLITUS - Lienardi, Aurellia R; Suwasanti, Niluh; Dewi, Dewa AL (JOURNAL OF WIDYA MEDIKA JUNIOR, 2021)
Introduction: Diabetes mellitus (DM) is a metabolic disease that can cause complications in the form of damage to male reproductive organs, such as decreased sperm motility and cell count, impaired spermatogenesis, and erectile dysfunction. A measurement that can be done to detect male reproductive disorders is to measure the thickness of the seminiferous tubule epithelium. Herbal medicines can be used to support treating diabetes. Studies have claimed that African bitter leaf helps in treating DM and its complications.Purpose: This study aims to determine the effect of African bitter leaf extract on epithelium thickness of seminiferous tubules in rats with DM.Method: True Experimental with Post-Test Only Control Group Design using Rattus norvegicus. Rats were divided into five groups, with six rats in each group. Rats were administered with a single dose of alloxan 150 mg/kg BW/IP. Group K is diabetic rats given glibenclamide 0,63 mg/kg BW. Group P0 are diabetic rats given CMC 0,1% 0,7 ml. Group P1 are diabetic rats given African bitter leaf extract 100 mg/kg BW. Group P2 are diabetic rats given African bitter leaf extract 200 mg/kg BW. Group P3 are diabetic rats given African bitter leaf extract 400 mg/kg BW. Treatments were given with oral gavage for 14 days. Rats were dissected, and their testis was made as histological slides. Results are statistically tested with ANOVA.Results: The average epithelium thickness from group K are 79,61 Î¼m, group P0 are 59,96 Î¼m, group P1 are 71,87 Î¼m, group P2 are 67,31 Î¼m, group P3 are 63,95 Î¼m showed significant result (p=0,000).Conclusions: African bitter leaf extract affects epithelium thickness of seminiferous tubules, with group K, shows the best result, followed by group P1.